Sustainable Development and Green Modernization as Conditions for the Transition to a New Industrial Revolution - S. N. Silvestrov; Yu. V. Zinchenko (Мир новой экономики, 2018)
The article clarifies the contents of such phenomena as the development of “sustainable (green) industry”, “sustainable (green) energy”. Reveals their place in the unfolding processes of the fourth industrial revolution. Emphasized the main trends in “green” modernization in the production process of companies. Identified economic, environmental and social benefits as a result of carried out different scales of European and American industrial companies environmentally and socially responsible industrial policy on the principle of “Cradle to Cradle system”. Presented and analyzed examples of activities of specific companies engaged in a gradual transition to the principles of “green economy”. The article considers examples of international regulation, aimed at the development of sustainable development and the creation of conditions for the industrial revolution acceleration In this regard, significant to note the prospect of development of the corporate sector towards the wider application of renewable energy sources.